Analysis of the Protection of Civil Citizens' Rights against Violent Practices by State Security Personnel - Wijayanto, Aji Rahma (Universitas Negeri Semarang, 2017)
It is the responsibility of the state to ensure that everyone stands equally and is protected for the sake of creating human integrity that is naturally inherent in humans, universal and eternal as a gift that has been bestowed by God Almighty. With the emergence of the General Declaration of Human Rights as a joint commitment between global countries in protecting every basic right that is inherent in humans, protection of Human Rights is important as an indicator of the success of state governance. In practice, there are still frequent cases of human rights violations committed by one of them by state security personnel by carrying out violent practices aimed at civil society for a specific purpose, it is necessary to protect basic human rights for all people so that the goal is to create good state governance from the perspective of human rights. Human Rights achieved.